Model Pengembangan Industri Kreatif Kerajinan Batu Akik Klawing Berbasis Ovop (One Village One Product) - Muhammad Hery Santoso; Sulistiyasni Sulistiyasni; Endang Setyawati (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2019)
This study aims (1) to explore and promote Klawing Purbalingga agate as an innovative and creative local product, which has unique regional characteristics, and has a high image and competitiveness among other agate industries (2) Development of MSMEs (micro, small and medium-sized industries) especially the highly competitive Klawing agate industry in the domestic and global markets (3) Creating Bancar Village as a center for crafting Klawing Purbalingga agate, which is integrated and sustainable. This study uses a survey method with a qualitative and quantitative approach with the respondents involved are agate craftsmen / marketers in Bancar Village, & LGs Data collection is done using the triangulation method, which is a method consisting of; Observation, Documentation and Interviews (unstructured interviews, structured interviews using question guides and in-depth interviews) with stakeholders related to efforts to develop the Klawing agate industry in Purbalingga. Conclusion (1) The Agate Klawing handicraft industry center in Desa Bancar has the potential and feasibility to be designated as a superior creative industrial product in Purbalingga Regency. (2) The Klawing agate industry center in Bancar Village is suitable for use as an icon of Purbalingga agate industry with the OVOP approach. (3) Craftsmen are ready to develop Klawing agate handicrafts as a product of superior creative industries in Purbalingga Regency.